ISOLATION AND IDENTIFICATION SOME THEPATHOGENIC AGENTS FROM ACUTE SUPPURATIVEOTITIS MEDIA (ASOM) IN CHILDREN IN AL-DIWANIYACITY AND THEIR SENSITIVITY TEST AGAINST SOE OFANTIBIOTICS IN VITRO - J., Ebtesam (Iraqi Journal of Science, 2024)
The present study entalid collection of (50) ear swabs from children patientssuffering from Acute suppurative Otitis Media (ASOM) carried at the E.N.T sectionof the teaching hospital in AL-Diwaniya a City. Whose ages ranged between (1 day-5 years) during the Period from October 2006 until Jun 2007. The aim of these studyis to isolate dominant pathogenic causes and responsible of (ASOM) in Children andeffect of some antibiotics on this causes.Staphylococcus aureus bacteria was thedominant cause of Acute suppurative otitis media with the percentage of 49. 23%.Followed by Candida albicans with the percentage of 30.76%, Proteus vulgaris6.15%, Pseudomonas aeruginosa 4.61 B-haemolytic streptococci, KlebsiellaPneumoniae Haemophilous influeenzae, Staphylococcus epidermidis, Enterobacterclocase, Moraxella catarrhalis with percentage 1.53% Results showed that 80% ofthe infection cases were caused by one pathogenic factor and 20% of them but morethan one factor. The sensitivity test showed that staph. aureus bacteria had thehighest Sensitivity to vancomycin 96.87%, Amikacin 78.12%, Tobromycin 68.74%and ciprofloxacin 65%, While showed lowest sensitivity to Lincomycin 3.12% whileProyeus vulgaris showed highest sensitivity to vancomycin 100%, Trobromycin75%, Amikacin and ciprofloxacin with other antibiotic 50% and showed lowestsensitivity to Tetracyclin with other antibiotics 25%. Pseudomonas aeruginosabacteria showed highest sensitivity to vancomycin and Amikacin 100%. Tetracyclinand ciprofloxacin with other antibiotics 66.66% while showed lowest sensitivity toTobramycin and other antibiotics 33.33%. the results of synergistic antibiotics effecton Staph aureus showed the effect between Amikacin with (Tobramycin,ciprofloxacin and tetracycline) had a parentage of 90.47% whilethe synergistic,effect between Tobromycin and (Amikacin , ciprofloxacin and Tetracycline) hadapercentage of 42.85%.While synergistic effect on Proteus vulgaris showed the effectbetween Amikacin with (Tobromycin, ciprofloxacin and Tetracycline) hadpercentage of 50%. While synergistic effect between Tobromycin and (Amikacin,ciprofloxacin and Tetracycline) had a percentage of 66.66%. The results showed thatCandida albicans isolates had the highest sensitivity to Nystatin with inhibition zonerate (10, 11.8, 18.76) mm, Miconazole (0, 8, 15.3) mm, ketoconazole (10, 9.6,14.94)mm, Fluconazole (0, 9.6, 12.6) mm, Griseofulvin (0, 0, 6) mm.